If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + 3 = 1 Reorder the terms: 2(-4 + x) + 3 = 1 (-4 * 2 + x * 2) + 3 = 1 (-8 + 2x) + 3 = 1 Reorder the terms: -8 + 3 + 2x = 1 Combine like terms: -8 + 3 = -5 -5 + 2x = 1 Solving -5 + 2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 1 + 5 2x = 1 + 5 Combine like terms: 1 + 5 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 2(x+3)-3x=21-6x | | Y+8y=45 | | 11-1/3n=1/3n-1 | | 6=11y-8y | | -5n(-8x-6)=-6x-22 | | 20=12v-8v | | (k/3)-19=-26 | | n=1/9 | | (r-2)(r+16)=-6 | | r^2+14r-26=0 | | 2(11r+7)+1=1414(88r+60) | | 4a-5=-5a+11 | | 2y-3=y+8 | | 356+56x=-833 | | 3x+12=-4x-16 | | 34+x=170 | | x/4-y/5=1 | | g/-10=0 | | 12x+15x+15=x+8 | | 2x(9x-1)(2x+3)=0 | | (-1/2)^-4 | | 12x+15x-15=x+8 | | 12x-15x-15=x+8 | | 6x-4x-(7x+3)= | | -5(-(x/5)) | | 3h-5=33 | | -2y=6+4x | | -5-(x/5) | | 16-x^2=9 | | 2x-13=4x+11 | | -5*-(x/5) | | 567b-674-h=45 |